The role of vitamin D3 during orthodontic treatment – a literature review - Tokarska, Paulina; Marczyńska-Stolarek, Magdalena; Zadurska, Małgorzata (Forum Ortodontyczne / Orthodontic Forum, 2019)
The aim of orthodontic treatment is bone remodelling due to resorption and apposition within bone tissue. The efficacy of these processes is dependent on various factors including patient`s general health. Conditions predisposing to vitamin D3 deficiency are particularly noteworthy, because they can potentially interfere with the speed and safety of tooth movements. Aim. To present types of metabolic processes within bone tissue during orthodontic treatment and the influence of vitamin D3 on their progress. To attempt to establish indications for conducting biochemical and hormonal tests before implementation of orthodontic treatment. Material and methods. Researchers used PubMed and GoogleScholar data bases, American Journal of Orthodontics and European Journal of Orthodontics publications to collect material using key words: “vitamin D3”, “bone remodelling”, “orthodontic tooth movement”, “osteoclast activity”. Full text publications in Polish or English were included in the literature review. The bibliography has been supplemented with published book monographs regarding orthodontics and histology. In total, 41 references were included Results. Presence of the optimal levels of vitamin D3 are a necessary condition for an undisturbed process of histologic changes in the bone tissue during orthodontic tooth movement. A correct and predictable course of orthodontic treatment is dependent on the patient`s good general health. It is advisable to measure the vitamin D3 levels prior to treatment, particularly in patients with an increased risk of deficiencies. (Tokarska P, Marczyńska- Stolarek M, Zadurska M. The role of vitamin D3 during orthodontic treatment - a literature review. Orthod Forum 2019; 15: 50-7).